Contingency theory, climate change, and low-carbon operations management - Furlan Matos Alves, Marcelo Wilson [UNESP]; Lopes de Sousa Jabbour, Ana Beatriz; Kannan, Devika; Chiappetta Jabbour, Charbel Jose [UNESP] (Emerald, 2017)
Purpose: Drawing on the theory of contingency, the aim of this work is to understand how supply chain-related contingencies, arising from climate change, are related to changes in the organisational structure of firms. Further, the authors explore how this relationship influences the perception of sustainability managers on the adoption of low-carbon operations management practices and their related benefits. Design/methodology/approach: To achieve this goal, this research uses NVivo software to gather evidence from interviews conducted with ten high-level managers in sustainability and related areas from seven leading companies located in Brazil. Findings: The authors present four primary results: a proposal of an original framework to understand the relationship between contingency theory, changes in organisational structure to embrace low-carbon management, adoption of low-carbon operations practices and benefits from this process; the discovery that an adequate low-carbon management structure is vital to improve the organisations’ perceptions of potential benefits from a low-carbon strategy; low-carbon management initiatives tend to emerge from an organisation’s existing environmental management systems; and controlling and monitoring climate contingencies at the supply chain level should be permanent and systematic. Originality/value: Based on the knowledge of the authors, to date, this work is the first piece of research that deals with the complexity of putting together contingency theory, climate-change contingencies at the supply chain level, organisational structure for low-carbon management and low-carbon operations management practices and benefits. This research also highlights evidence from an emerging economy and registers future research propositions.
Keywords: Climate change; Emerging economies; Low carbon; Low-carbon economy; Sustainability; Sustainable innovation; Sustainable operations; Sustainable supply chain